Security and Defence in Europe
XXVI, 264 p. 16 illus., 11 illus. in color.
Keywords: This book argues that security and defense have never been true priorities in the European Union, and have constantly been marginalized by the elites since the Soviet Union collapsed and the Warsaw Pact disintegrated. Despite the official rhetoric, only a few tangible results can be presented concerning the operational readiness of European forces, and the EU’s inability to act was proven during the crises in the Balkans, NATO has experienced similar problems, as the majority of its members are EU countries. Both organizations have declared their resolve concerning the security and defense of their nations and territories, but, unfortunately, little has been done to lend these statements credence. In this context, the book analyzes several aspects of EU security and defense, including: the EU – NATO relationship, common defense policy and strategy, common capability building, common understanding of strategic changes, common operational planning and centrally synchronized exercises based on operational planning, etc. The member states have helped to make EU/NATO effective organizations, but unfortunately their individual interests and priorities constitute real challenges. This aspect should be discussed and addressed by political and military elites, scholars, analysts, students and the general public alike. .